INTERNALIZATION OF RESILIENCE CHARACTER AS A PROVISION TO FACE THE LEARNING CHALLENGES OF ELEMENTARY SCHOOL STUDENTS IN THE DIGITAL-GLOBAL ERA - Ika Wahyuningsih,; Sedya Santosa, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract This study explores how teachers at an elementary school in East Java internalize the character of resilience to tackle the challenges faced by students in the global digital era. The research was conducted at a Madrasah Ibtidaiyah Unggulan in the Ponorogo area. Data was collected through interviews with one informant. The study found that post-Covid-19 challenges have caused academic delays and gadget addiction among students. Many students were exposed to adult content videos, particularly on online gaming platforms. The study identified several steps teachers take to internalize student learning resilience, including instilling responsibility, recognizing students' emotions and fostering interactive communication, appreciating students' efforts and learning processes, offering opportunities for new and challenging tasks, and adopting a personal approach. These findings highlight the importance of teachers in helping students navigate the complexities of the digital era and develop resilience in the face of challenges.